2002
DOI: 10.1093/oxfordjournals.rpd.a006098
|View full text |Cite
|
Sign up to set email alerts
|

The Unified Interaction Model Applied to LiF:Mg,Ti (TLD-100): Properties of the Luminescent and Competitive Centers during Sensitisation

Abstract: An attempt is made to predict/interpret theoretically the experimentally measured values of f(D) and S(Ds)/So for composite peak 5 in TLD-100. using the Unified Interaction Model (UNIM) with identical values of the UNIM parameters for both sets of experimental data. Although an excellent fit can be obtained to the experimental f(D) data over the entire dose region where f(D) is greater than unity. i.e. from 5 Gy to several thousand Gy, a satisfactory fit to both sets of data is found to require different value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In the LT model all trapped carriers will recombine with adjacent RCs at an appropriately high temperature. However, we can enrich the model by adding the possibility of separation of trapped hole-electron pairs in a way similar to that for the most popular LiF : Mg, Ti detector: for example, Nail et al [14] and Horowitz et al [15] considered that only peak 5a relates to the geminate recombination (i.e. the LT).…”
Section: The Model Of Sltsmentioning
confidence: 99%
“…In the LT model all trapped carriers will recombine with adjacent RCs at an appropriately high temperature. However, we can enrich the model by adding the possibility of separation of trapped hole-electron pairs in a way similar to that for the most popular LiF : Mg, Ti detector: for example, Nail et al [14] and Horowitz et al [15] considered that only peak 5a relates to the geminate recombination (i.e. the LT).…”
Section: The Model Of Sltsmentioning
confidence: 99%
“…• The lack of constraints (e.g. early or late entry into saturation) on the dose-dependence of the competitor required to explain the supralinearity of peak 5 [31]. It is demonstrated that the competitor need not enter into early saturation in order to promote supralinearity.…”
Section: Non-linear Effects In the Tl Dose Responsementioning
confidence: 99%
“…The basic idea of the UNIM is that the linear response at low dose arises from geminate recombination in a localized entity. For gamma rays and electrons, the localized entity is the coupled/spatially correlated TC/LC pair [22,[30][31][32]. Note that the supralinearity is not present in LiF : Mg,Cu,P (a linear/saturating dose response is observed- figure 14) due to the absence of Ti and, consequently, the lack of formation of the TC/LC coupled pairs.…”
Section: Non-linear Effects In the Tl Dose Responsementioning
confidence: 99%
See 1 more Smart Citation
“…After several decades of investigation, the following salient features of OA in LiF:Mg,Ti have emerged: There are eleven clearly identifiable optical absorption bands spanning the energy range from 2.84 eV to 10.97 eV (Nail et al, 2002). Of these, only two bands have been convincingly correlated with TL trapping centers (TCs); the intense 4.0 eV band with composite peak 5 and the 3.24 eV OA band with peaks 2 and 3 which have been attributed to (Mg-Li vac ) trimers and dipoles respectively (McKeever, 1984).…”
Section: Introductionmentioning
confidence: 99%